DINAMIKA LANSIA PANTI SOSIAL TRESNAWERDA KHUSNUL KHOTIMAH DI PEKANBARU - Deni Fransisco; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Tresnawerda Khusnul Khotimah Nursing Home Pekanbaru. The purpose of this study is to determine dynamics of elderly. Topic in this research studied social interaction and self-adjustment of elderly. The key informants consisted by 3 elderly, 1 head of UPT and 1 dormitory used qualitative descriptive method with deep interview investigation. It can be concluded; 1) The social interaction of elderly with their family of origin caused by economic limitations, no longer closer family, the institution has communication service so that between elderly and their family can contact or visit. The interaction of fellow elderly in the orphanage consists of special schedule in everyday life like eating together, religious guidance, counseling guidance, recreation, elderly gymnastics, nursing care, and handicraft whose purpose is to fill the activity and build interaction among fellow elderly in the orphanage. 2) Adjustment of the elderly is very good because most elderly come from Riau have background, custom, culture, and language which almost same so that both old elderly and elderly who have long stay no trouble to communicate each other. Adaptation constraints experienced in the adjustment of the elderly is still sad due far from their family, the trauma of being left by his family, prefer to be alone, difficult to follow the guidance of religion because they was less religious life, and did not want to follow elderly gymnastics.Keyword: Social interaction, Self-adjustment, Elderly